Copyright for Digital Error, Overcoming Revenge Porn on X Application through the Lens of Policy and Laws - Fauzan, Alriansyah Sakhi; Purwadi, Hari (International Journal of Sustainability in Research, 2024)
The advancement of digital technology and social media platforms has brought big changes in communication and information sharing. However, this digital transformation also brought a new type of sexual assault, including revenge pornography. This article analyzed the challenges of laws and policy procedures for revenge porn, with a focus on how the international law can overcome this digital copyright infringement. By analyzing the existing legal framework and proposing a comprehensive policy, this article aimed to give a strong response to combat revenge porn effectively, secure privacy, and preserve individual dignity in a digital era. The methodology used in this study was the approach of the juridical, normative, and comprehensive analysis of the law principles and the regulations related to revenge porn. The methodology covered identification methods, of the laws, doctrine, and existing regulations aiming at showing the exact weaknesses, suggesting law modification, and giving effective perspective to increase the law enforcement in overcoming revenge porn in the digital era. Besides, this study used literature reviews and applied the perspectives of juridical normative to evaluate the legal framework in handling revenge porn on social media platforms Overcoming revenge porn in Indonesia required a dedicated approach and multi-perspectives. Indonesia could protect the copyrights for individuals better and make sure that they would be in charge of committing a digital error.